Analisis Kesesuaian Hukum Dalam Proses Pengadaan Barang/Jasa Pemerintah Pada Pekerjaan Jasa Konsultasi Penyusunan Naskah Akademis dan Ranperda Air Limbah Domestik Dalam Perjanjian Antara Dinas Pekerjaan Umum dan Penataan Ruang Kota Pekanbaru dengan PT Pus - Sari, Komala (Prosiding, 2024)
The contract that occurred between the Public Works and Spatial Planning Office (PUPR) of Pekanbaru City and PT Pusat Pendidikan Nasional is a consulting service contract for the preparation of academic manuscripts and the regional regulation on domestic waste water of Pekanbaru City in the form of a contract in the form of a Work Agreement (SPK) worth Rp. 93,610,000 signed by the Commitment Making Officer (PPK) of the Pekanbaru City PUPR Office with the director of the National Education and Training Center. The implementation of this consulting service contract deviates from the rules contained in Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods and Services. Judging from the Good Faith Theory in contracting, the implementation of this contract is contrary to the Good Faith principle of Article 1338 (3) BW, because the PPK has contracted when the budget is not yet available for payment of achievements, so it includes doing frod/tricks that hide a fact. If it is related to the principle of contractual balance, the contract is considered unfair, because as a process, an ideal contract should be able to accommodate the fair and equitable exchange of interests of the parties at every phase or stage of the contract. This contract does not include in detail the fine clause if the service user defaults or the compensation that should be received by the service provider if he is late in receiving work performance. In this case, the Public Works Office of Pekanbaru City has defaulted on the implementation of the contract and was negligent of its obligations to the detriment of the National Education and Training Center. Until finally the conflict resolution was carried out with the Yielding strategy, namely the service provider relented and was willing to be paid without receiving compensation. So it can be concluded that the PBJ activities at the City/Pekanbaru PUPR Service are not in accordance with the legal procedures/mechanisms for Procurement of Goods/Services.